Phenobarbital induced Stevens-Johnson syndrome: a case report - Ramineni, Hari Babu; Eluri, Pravallika; Vipparla, Kumudini; Suryadevara, Vidyadhara (International Journal of Research in Medical Sciences, 2017)
Stevens-Johnson Syndrome (SJS) is a life-threatening acute hypersensitive reaction affecting the skin and mucous membranes. We report a case with SJS likely induced by phenobarbitone during the switch of sodium valproate and phenobarbitone regimen. The patient reported fever with fluid-filled lesions all over the body and redness and burning sensation of both the eyes. Peeling of the skin due to rupture of the fluid-filled lesions and pigmentation on the skin for 10 days. Based on a physical examination and laboratory findings, he was diagnosed with Phenobarbital induced Stevens-Johnson syndrome. The patient was administered systemic steroid therapy and treated symptomatically and finally replaced with phenobarbitone and sodium valproate. During the hospital stay, the patient appeared normal and the skin lesions disappeared, after two weeks of treatment.